Gaṅgeśa's theory of indeterminate perception Nirvikalpakavāda - Bhattacharyya, Sibajiban (Indian Council of Philosophical Research : Distributed by Munshiram Manoharlal Publishers, 1993)
Basic work on Hindu logic and epistemology of the neo-Nyaya school in Hindu philosophy; portion of Tattvacintāmaṇi deals with perception.